2006
DOI: 10.1158/0008-5472.can-06-1617
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of an Oncolytic Adenovirus-Delivered Oncogene Small Interfering RNA

Abstract: Despite successes in animal models, cancer gene therapy with small interfering RNAs (siRNA) is hindered by the lack of an optimal delivery platform. We examined the applicability of the replication-competent, oncolytic adenovirus, ONYX-411, to deliver a mutant K-ras siRNA transgene to human cancer cells. Proof-of-principle studies showed an additive tumor growth-inhibitory response through siRNA-mediated K-ras knockdown and ONYX-411-mediated cancer cell lysis. A novel construct, termed Internavec ( for interfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 39 publications
0
50
0
1
Order By: Relevance
“…Improving development of tumor-specific promoters to limit viral replication in malignant tissue may enable greater confidence in the utilization of replication aggressive viruses. 14,[188][189][190][191][192][193][194][195][196][197] Ultimately these modifications will likely need to be built into viral constructs that deliver molecular targeted therapeutics [198][199][200][201][202] and can be utilized in combination with traditional therapeutics, [203][204][205][206][207][208] thereby creating a 'super' virus.…”
Section: Resultsmentioning
confidence: 99%
“…Improving development of tumor-specific promoters to limit viral replication in malignant tissue may enable greater confidence in the utilization of replication aggressive viruses. 14,[188][189][190][191][192][193][194][195][196][197] Ultimately these modifications will likely need to be built into viral constructs that deliver molecular targeted therapeutics [198][199][200][201][202] and can be utilized in combination with traditional therapeutics, [203][204][205][206][207][208] thereby creating a 'super' virus.…”
Section: Resultsmentioning
confidence: 99%
“…Viral DNA quantification was performed by real-time PCR (qPCR MasterMix Plus; Eurogentec, Seraing, Belgium) using 100 ng of liver DNA and adenoviral hexonspecific primer probes as described before. 44 18S Genomic Control Kit (Eurogentec) served as internal control. For the investigation of liver damage, explanted livers were examined macroscopically, and ALT/AST activities were determined in serum samples from treated mice using the AST/ALT enzymatic assay kit (Bioo Scientific) according to the manufacturer's protocols.…”
Section: Targeting P53-dysfunction By Adp53sensormentioning
confidence: 99%
“…RNAi directed against mutated KRAS showed anti-tumor activity [15], limited the aggressive phenotype of the tumor cells [16] and potentiated gemcitabine antitumor activity [17]. Preclinical studies showed encouraging results with viral delivery systems such as oncolytic adenovirus [18]. However, this strategy has not been further tested in phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%